Functional value cognition of Cornus officinalis grape wine - WANG Zijin, YANG Hecai, YUAN Jiawei, ZHANG Yonggang (Zhongguo niangzao)
With the development of Chinese economy, people's pursuit of a better life is gradually moving towards health and wellness, and Cornus officinalis grape wine has come into being. Using means-endchain (MEC) theory, 20 experimenters were effectively interviewed by soft ladder method. The "attribute-result-value" cognitive system of consumers for C. officinalis was studied, and the consumption value meaning matrix and hierarchical value map were constructed. The survey results showed that product attribute cognition was composed of origin, health function, refreshment, customs and etiquette, and personal habits, product result cognition was composed of physical strengthening, health, comfort and spirit. Product value cognition was composed of health, socialization, confidence and achievement, forming a market cognitive structure of "C. officinalis grape wine- health-wellness-socialization-confidence and achievement". This provided a psychological anchor path for the development of the C. officinalis grape wine market.